Psychological Resilience and Its Relationship to Achievement Motivation among Physical Education Teachers for People with Special Educational Needs in the Jerusalem Governorate (Damu Journal of Sport Sciences, 2025)
Objective: The study aimed to identify the level of psychological resilience and its relationship to achievement motivation among physical education teachers for people with special educational needs in the Jerusalem Governorate, and the relationship between them. It also aimed to identify differences in the level of psychological resilience and achievement motivation among teachers according to the variables of gender and years of teaching experience. Method: The study was conducted on a convenient sample of (67) male and female physical education teachers for people with special educational needs, representing approximately (56%) of the study population. The researchers used a descriptive, correlational, and analytical approach due to its suitability for the nature of the study. To collect data, a psychological resilience tool was used.Results: The study results showed that the level of psychological resilience and achievement motivation among physical education teachers for people with special educational needs in the Jerusalem Governorate was high, with response averages of (3.66, 3.80), respectively. The results also revealed a statistically significant relationship between the level of psychological resilience and achievement motivation among teachers, with Pearson's correlation coefficient values being (0.75, 0.63), respectively. The results also indicated statistically significant differences in the level of psychological resilience and achievement motivation among physical education teachers for people with special educational needs in the Jerusalem Governorate attributed to the gender variable, in favor of (males). However, there were no statistically significant differences in the levels of psychological resilience and achievement motivation among teachers based on the variable of years of teaching experience.